NET PROFIT, COMPANY VALUE, AND DIVIDEND POLICY: EMPIRICAL STUDY ON CONSUMER NON-CYCLICAL COMPANIES - Nurmala, Putri; Adiwibowo, Akhmad Sigit (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
This study aims to provide empirical evidence that net income and firm value affect dividend policy in the consumer non-cyclical sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. This study's independent variables are net income and company value. Meanwhile, the dependent variable is dividend policy. The sample was selected using the purposive sampling method to obtain 18 companies that met the criteria with an observation period of 5 years. The data used is secondary. Data analysis using multiple regression analysis. From this research, the conclusion is that net income does not affect dividend policy. Meanwhile, company value has a positive effect on dividend policy.